HADIS TENTANG KEIMANAN ORANG YANG BERBUAT MAKSIAT - Muhammad Nuh Siregar (UIN Sumatera Utara Medan, 2019)
Immoral acts or great sins committed by someone does not cause a person to become an infidel. But he is still said to be a believer despite his lowest level of faith. Because based on the Hadith of a believer's faith are multilevel and can be increased and can also be reduced. A person's faith will increase when he carries out obedience, carries out the commands of religion and carries out other goodness. Conversely, one's faith will decrease when he commits sin and or disobedience. On the basis of this, it was concluded that the faith of the theology of the Khawarij, Muktazilah and others which determined that one's faith was seen from his deeds could not be held captive. But the true faith is tasdiq (accept) in the heart that